Perlakuan Air Panas untuk Pengendalian Penyakit Busuk Buah Salak selama Penyimpanan - Anis Mutirani; Giyanto Giyanto; Efi Toding Tondok (PERTETA, 2023)
Fruit rot disease is one of the important diseases that causes a high yield loss of snake fruit during storage. The alternative of postharvest process to maintain the quality of snake fruit is hot water treatment. This study aims to obtain a combination of soaking time and temperature that can control fruit rot disease of Pondoh snake fruit. The treatment consisted of 45, 50 and 55°C for 5 and 10 minutes and control. The results showed that hot water treatment had a significant effect on the snake fruit. Temperature of 50°C for 5 minutes is more effective in preventing the appearance of disease symptoms up to 10th days of storage, compared to controls which started to show symptoms on the 2nd day. Isolation of fungal pathogen from diseased control were found 4 fungi, i.e Thielaviopsis paradoxa, Aspegillus flavus, Fusarium sp. and Penicillium sp., while T. paradoxa and A. flavus are still found on treated diseased samples with hot water treatment. Hot water treatment did not affect the water content and total fruit acid but impacted to the weight loss and was able to maintain the hardness value and the panelist's preference level based on organoleptic tests.